Maleic and l-tartaric acids as new anti-sprouting agents for potatoes during storage in comparison to other efficient sprout suppressants - Ekta Bhattacharya (Nature Portfolio, 2021)
Abstract Inhibiting sprouting of potatoes is an interesting subject needed for potato storage and industry. Sprouting degrades the quality of tuber along with releasing α-solanine and α-chaconine, which are harmful for health. Sprout suppressants, available in the market, are either costly or toxic to both health and environment. So, there is a need for developing countries to explore new sprouting suppressant compound which is cheap, non-toxic and reasonably efficient in comparison to commercial ones. We have established that simple maleic acid and l-tartaric acid are effective sprout suppressing agents. Both can hinder sprouting up to 6 weeks and 4 weeks post treatment respectively at room temperature in dark. These do not affect the quality parameters, retain the moisture content and maintain the stout appearance of the tubers along the total storage period. Thus maleic acid and l-tartaric acid would qualify as alternative, cheap, efficient sprout suppressant for potato storage and processing.